Multi-layer endoscopic suturing: a novel method of gastric fistula closure - Jovani, Manol; Zhang, Linda; Huang, Yuting; Kumbhari, Vivek (Endoscopy International Open, 2021)
Background and study aims Current endoscopic methods of treating gastric fistulas are either too complex or have high rates of recurrence. We aimed to provide a novel endoscopic method for robust fistula closure.Patients and methods This was a single-center, retrospective study of five patients who underwent multi-layer endoscopic suturing for closing of a chronic fistula (> 4 weeks). Devitalization of the fistula tract was achieved with argon plasma coagulation, followed by endoscopic suturing of the fistula. Then, endoscopic suturing of the gastric wall surrounding the fistula was performed, creating an overlay of healthy gastric mucosa around the fistula.Results Technical success (fistula closure on the day of the procedure) was achieved in all five patients, with no complications. After a median follow up of 5 months (range 2–23 months), there was a 100 % clinical success rate (no fistula recurrence).Conclusions Our single-operator method of multi-layer endoscopic suturing provides a robust fistula closure with minimal to no risk of recurrence. In light of limitations of current fistula closure methods, further investigations are warranted to better define long-term outcomes with it compared to alternative methods.